Community forestry in Nepal: Women and collective action - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Community forestry has remained Nepal's forest management strategy since its introduction in 1978. Local communities make decisions regarding the use, distribution and management of forest resources, and are organized into Community Forest User Groups (CFUGs) where each CFUG elects a set of officers composed of a chair-person, a vice-chairperson, a secretary, and a treasurer. There are currently 14,000 CFUGs controlling approximately 1.2 million hectares, or 25 percent, of Nepal's forest area. Forest conditions have improved upon the implementation of this strategy but concerns are being raised regarding equity and the role of women.